Determination of Biodegradation Rate of Bioplastic with Controlled Environment - Dwiyana, Amelia; Sutanto, Sutanto; Fathurrahman, Muhammad; Herlina, Eka (Helium: Journal of Science and Applied Chemistry, 2023)
The use of synthetic plastics in everyday life has a negative impact but can be reduced in effect, if replaced with biodegradable plastics. Polymer biodegradation can occur because of microbiological infestation of the material. Microorganisms could produce various kinds of enzymes that can react with polymers. This study aims to study the effect of adding organic matter spearhead bacteria on the biodegradation rate in test samples with the help of Bacillus sp bacteria and the bacterium Pseudomonas sp. In this case, bioplastic samples were characterized using Fourier Transform Infrared (FTIR) spectroscopy and continued with quantitative analysis using gravimetric methods to determine biodegradation rates based on CO2 weight. The results of the characterization test study showed that the test sample containing cellulose is characterized by the presence of glycosidic -OH, -CH, and C-O functional groups. The determination of the rate of biodegradation gave the value of the rate constant microcrystalline cellulose as a positive control of 0.0489 day-1, Bioplastic A without inoculum addition of 0.0451 day-1 while Bioplastic A with the addition of inoculum by 0.0423 day-1 . Meanwhile, Bioplastic B without inoculum addition is 0.0254 day-1, and bioplastic B with inoculum addition is 0.0391 day-1.